THE CHARACTERISTICS OF VETIVER GRASS AS A PHYTOREMEDIATOR PLANT IN DOMESTIC GREYWATER TREATMENT - Astuti, Jovita Tri; Sriwuryandari, Lies (LIPI Press, 2016)
Source separation of domestic wastewater into greywater (GW) and blackwater (BW) streams is important in decentralizing treatment due to its different characteristics. GW is generated from bathroom, washing machine,kitchen sink, and vehicle washing. Meanwhile, BW is produced from toilet, urinal or bidet. In developing countries, untreated wastewater is widely used in agricultural and risk to human health and living organisms. The appropriate treatment is required to prevent water degradation. Phytoremediation is a sustainable way to mitigate pollution with using plant. This study was conducted to observe the characteristics of vetiver grass as phytoremediator for GW. There are two factors of treatment. First is growth media (M), i.e. tap water (TW) as control (M0) and GW (M1). The second is vetiver (V), i.e. without (V0) as control and with planting (V1). Three glass aquariums are used for each treatment as replicates. Eight individual stem bases of vetiver were placed at aquarium and allowed hydroponically growing. At harvesting (49th day), vegetative organs were collected and observed separately, i.e. root, stem and leaf. Pollutant removal was calculated by comparing the content before and after treatment of media with vetiver. Cultivation of vetiver in GW (M1V1) could increase the root number, total root length, and total root diameter as much as 54%, 92.2%, and 51%, respectively. Individual root length was in the range of 2.3-78.5cm and root diameter was 0.35-2.10mm. Compared to the initial, stem number increased 99%, while leaf number increased 4 times. Root/Shoot (R/S) ratio was 0.80±0.14. Polutant removal of GW by vetiver achieved 72.86% BOD5; 65.51% COD; 66.55% TN; 67.67% TP; 80.77% Fe; 71.43% Zn; 60% Pb; 65.81% detergent, and 100% phenol. Vetiver could reduced TPC 29.13%, MPN coliform 78.18%, and MPN fecal coli 91.54%. After treated with vetiver, GW complied to criteria of water Class IV that can used for irrigation in agricultural.